Institutional reform and depositors' portfolio choice: Evidence from bank account data - Michael Berlemann; Marc-André Luik (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
This paper studies the effect of institutional reform on the decision to hold risky assets at the example of the natural experiment of German Division and Reunification. We present empirical evidence indicating that even 16 years after German Reunification risky portfolio choice and composition differed systematically between East andWest German bank customers, even after controlling for sociodemographic factors. While these differences are especially pronounced for bank customers with experiences in the former communist system, even the younger generation of East Germans still differs remarkably from their West German counterpart in terms of risky asset choice. Thus, informal institutions tend to have more long-lasting effects on portfolio behavior as previous studies seem to imply.
Keywords: G21; J1; L1; O16; P36; 330; institutional reform; stockholding puzzle; portfolio choice; bank data